Development and validation of a diagnostic system for the detection of specific antibodies and antigens against Porcine Epidemic Diarrhea Virus - Dong, Bo; Yang, Chuanjiang; Zhang, Haiyan; Jiang, Kesong; Yang, Xiaoyan (The Thai Journal of Veterinary Medicine, 2020)
Porcine epidemic diarrhea virus (PEDV) is highly pathogenic and infects suckling piglets, thereby imposing a major burden on the swine industry all over the world. The aim of this study is to develop two ELISA systems for the detection of antigens and antibodies against PEDV in pigs. The PEDV N recombinant protein was expressed and was used as the coating antigen to establish an indirect ELISA for detecting PEDV-specific antibodies in pig serum. Moreover, MAb was induced with the recombinant N protein and used for sandwich ELISA to specifically test for PEDV. The specificities of the two ELISAs were validated by comparing the results with other viruses and the reproducibility was evaluated by intra-assay or inter-assay variation. The diagnostic sensitivity and specificity also were evaluated by the receiver operating characteristic (ROC) curve. The two ELISAs both indicated acceptable reproducibility. Neither ELISA cross-reacted with other viruses. ROC curve analysis revealed 100.0% sensitivity and 95.2% specificity of the iELISA, 100.0% sensitivity and 90.0% specificity of the sELISA. Consequently, this work indicates that these two ELISAs can be used clinically to diagnose PEDV.